Collective Bargaining Attitudes of Registered Nurses in the United States and Canada: A Wisconsin-Ontario Comparison - Ponak, Allen; Haridas, T. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This paper compares the attitudes to collective bargaining of a sample of Ontario and Wisconsin registered nurses. Contrary to expectations (in view of the general low rate of American nursing unionism), the Wisconsin nurses who where surveyed viewed collective bargaining at least as favourably as their Ontario counterparts.